WTO accession: structural changes to China's exports. - Cheong, Chu Lei. (2008)
China’s WTO accession has generated much debate on its influence on her exports. This paper shows empirically that WTO has not only affect China’s exports positively, but has also made significant changes to the structure of the export. The main reasons include that her admission into WTO has decreased the trade barrier with other countries and increased market access. By estimating export equations of significant periods from 1994Q4 to 2007Q1 using OLS, we have found that income elasticities processed exports have risen while the price elasticities has mixed results for processed and ordinary exports.